Generalized Anxiety Disorder in Brazilian university students during the COVID-19 pandemic - Soares, Fernanda Farias; Brilhante, Andreia Fernandes; Cruz , Andrey Oliveira da; Sinhorin, Gustavo Henrique; Sinhorin, Géssica Thais; Cruz, Jene Greyce Oliveira da; Lago, Rozilaine Redi; Brandt, Marisol de Paula Reis; Melchior, Leonardo Augusto Kohara (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2023)
Objective: this study assessed the anxiety levels of Brazilian university students during theCOVID-19 pandemic. Methodology: the Generalized Anxiety Disorder 7-item scale was used tomeasure the anxiety levels of 1,837 respondents to an online research questionnaire. Results:the participants were mostly women aged from 18 to 27 years old, enrolled in graduate programsat public universities, living with people considered at risk for COVID-19, and earning familyincomes of 1 to 3 minimum wages. More than 75% of the participants reported some level ofanxiety, with 23.08% reporting severe levels, while only 24.93% experienced normal anxietylevels. The ordinal logistic regression identified that being a young woman with a low incomecould affect the anxiety level. Additionally, students from the field of humanities, well-informedstudents and those at risk for COVID-19 were significantly more likely to experience anxiety.Conclusion: the mental health of Brazilian university students, particularly certain groups, wasaffected by the COVID-19 pandemic and requires specific attention and care.